The Shaping of Sustainable Careers Post Hearing Loss - Baldridge,David; Kulkarni,Mukta (Human Relations, 2017)
Through this interview-based study with 40 respondents in the United States we have outlined enablers of career transitions and sustainable careers for professionals who have experienced severe hearing loss as adults. To sustain careers after adult onset disability, respondents engaged in a quest for meaning and big picture answers to ‘who am I?’ and ‘am I still successful?’ This included redefining themselves – e.g. I am now both a person with a disability (disability identity) and a successful professional (professional identity) – and career success (e.g. now I care about service to society as much as I care about material artifacts). Respondents also adopted new work roles where disability was a key to success (e.g. becoming an equal employment officer) and utilized social networks to continue being successful. Such redefining of work and networks supported the aforesaid quest for meaning and big picture answers. Findings not only indicate how individuals experience career success after a life-changing event but also help defamiliarize extant notions of ableism in workplace contexts.
Keywords: Management